2016
DOI: 10.2217/pgs-2016-0131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SNPs in CYP450 in Chloroquine/Primaquine Plasmodium Vivax Malaria Treatment

Abstract: Future studies should be performed to access the extent of CYP2C8, CYP2C9 and CYP3A5 gene polymorphisms influence on cloroquine/primaquine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…A recent study reported for the first time the influence of the CYP2C8 gene on clearance in patients with chloroquine/primaquine therapy. 121 Wild-type CYP2C8 homozygous individuals achieved greater reduction in gametocytes as compared to individuals without this genotype. 121 Another study demonstrated CYP2D6 polymorphisms in systemic lupus erythematosus patients treated with hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A recent study reported for the first time the influence of the CYP2C8 gene on clearance in patients with chloroquine/primaquine therapy. 121 Wild-type CYP2C8 homozygous individuals achieved greater reduction in gametocytes as compared to individuals without this genotype. 121 Another study demonstrated CYP2D6 polymorphisms in systemic lupus erythematosus patients treated with hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 91%
“… 121 Wild-type CYP2C8 homozygous individuals achieved greater reduction in gametocytes as compared to individuals without this genotype. 121 Another study demonstrated CYP2D6 polymorphisms in systemic lupus erythematosus patients treated with hydroxychloroquine. CYP2D6*10 allelic variants were found to be significantly associated with altered metabolism of HCQ.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…G6PD deficiency prevalence was estimated in 4.5% in the Western Brazilian Amazon and was related to decreased malaria susceptibility [ 8 ], which led us to develop studies for the implementation of a rapid test to detect the G6PD deficiency in patients diagnosed with malaria. Comparatively, the impact of other pharmacogenomic polymorphisms in the response and/or disposition of primaquine and chloroquine in P. vivax malaria patients has drawn less attention [ 9 ]. However, an original observation by Bennet et al [ 10 ] followed by a case report by Ingram et al [ 11 ] triggered considerable interest in a novel aspect of the pharmacogenomics of P. vivax malaria.…”
Section: Introductionmentioning
confidence: 99%
“…PGx studies of CYP2C9 , not related to anticoagulants, explored associations with the antimalarial effect of chloroquine/primaquine therapy and the efficacy of piroxicam for post‐operative pain, with negative results in both cases.…”
Section: Resultsmentioning
confidence: 99%